Strengthening Emergency Maternal and Neonatal Care A Provincial Initiative to Improve PONED Capacity in Central Sulawesi, Indonesia - Risnawati Arif (Professorline, 2025)
Maternal and neonatal mortality remain major public health concerns in Indonesia, particularly in rural and under-resourced regions. Despite national policies promoting emergency obstetric and neonatal care (PONED), disparities persist due to limited human resource capacity, inadequate facility preparedness, and weak referral coordination. This study describes the design, implementation, and outcomes of the GADAR PONED 2025 initiative, a provincial-level program aimed at improving the quality and responsiveness of emergency maternal and neonatal services in Central Sulawesi, Indonesia. Using a descriptive and participatory approach, the program integrated structured training, simulation-based learning, and inter-facility coordination across 15 district-level puskesmas. The intervention involved multidisciplinary teams of doctors, midwives, and nurses, emphasizing clinical skills, communication, and decision-making in emergency scenarios. Data were drawn from training evaluations, supervision reports, and stakeholder feedback. Findings showed a significant improvement in participants’ clinical competency, teamwork, and confidence in managing obstetric and neonatal emergencies. Facility assessments indicated enhanced preparedness through better resource allocation and referral response times. The establishment of communication networks among PONED teams and hospitals further reduced delays in emergency handling. The GADAR PONED 2025 initiative demonstrates that integrating human resource training with system preparedness and referral coordination can effectively strengthen maternal and neonatal emergency care. This provincial model provides a practical framework for scaling up sustainable, decentralized health interventions aligned with Indonesia’s efforts to achieve the Sustainable Development Goals (SDG 3.1 and 3.2).